What Harry Discovered: A Review of Harry Stottlemeier's Discovery - Davidson, Janet E. (Analytic Teaching, 2014)
Introduction: "It probably wouldn't have happened if Harry hadn't fallen asleep in science class that day." So begins the novel Harry Stottlemeier's Discovery. "It" refers to Harry's embarrassing himself by giving a stupid answer to his science teacher's question about comets. But we are all lucky Harry fell asleep that day, or at least that his mind wandered off, because if he hadn't who knows whether the novel would have been written, or whether today we would have the PHILOSOPHY FOR CHILDREN program of Matthew Lipman, of which Harry is the pilot novel that started the program.